5.3 Postnatal Testing for persistence of abnormal glucose metabolism after Gestational Diabetes: Fasting Plasma Glucose or Oral Glucose Tolerance Test?. (9th June 2014) - Mudalige, NL; Thornhill, L; Sinha, S; Cotzias, C; Dixit, A
Abstract : Introduction: Gestational Diabetes Mellitus (GDM) is a multisystem disorder that increases the risk of complications for both mother and child. In most cases, GDM resolves postnatally and NICE recommend a fasting plasma glucose (FPG) measurement at the 6-week postnatal check, to ensure this. However we believe an oral Glucose Tolerance Test (OGTT) would be a more sensitive marker of abnormal glucose metabolism compared to FPG, especially as the long-term cost of managing impaired glucose tolerance (IGT) or type 2 Diabetes Mellitus (T2DM) is significant. Methodology: Postnatal OGTT data for women with GDM, delivering between 09/2008–09/2013 at West Middlesex Hospital, was collected. Of 1115 women, 786 attended for postnatal OGTT (70.4% uptake). Results: Of 786 women undergoing a 6-week postnatal OGTT, 133 (16.9%) had an abnormal result: 34 were diagnosed with T2DM, 34 with elevated FPG alone and 32 with both elevated FPG and 2-hour value. Strikingly, 67 (50.3%) had an elevated 2-hour value at OGTT with a normal FPG: 59 with IGT (2-hour value 7.8–10.9 mmol/L) and 8 with T2DM (2-hour value ≥11 mmol/L), all of which would have been misdiagnosed as normal. Furthermore, 5 women with impaired fasting glucose (6.1–6.9 mmol/L) but a 2-hour value indicative of T2DM would be misdiagnosed. Conclusion: Half of women diagnosed with GDM who have persistent IGT/T2DM are overlooked under current UK guidelines. Given the increasing prevalence of T2DM and its long-term complications, this is a missed diagnostic opportunity. Therefore we recommend that all women with GDM should be offered an OGTT postnatally.